Reading Self-Concept and Reading Anxiety in Second Grade Children: The Roles of Word Reading, Emergent Literacy Skills, Working Memory and Gender - Katzir, Tami; Kim, Young-Suk G.; Dotan, Shahar (Frontiers in Psychology, 2018)
Background 3 Most studies in the field of reading have focused on the linguistic and cognitive factors. Less is 4 known about the affective aspects of reading in young readers, such as self-perceptions of 5 reading, and reading related anxiety. 6 Aims 7 This study aimed to shed light on the direct and indirect relations between reading and related 8 skills (working memory, emergent literacy skills, word reading accuracy and rate, and gender) as 9 sources of reading affect (reading self-concept and anxiety). 10 Sample 11 A total of 115 Hebrew speaking second graders participated in this study. 12 Methods 13 A set of measures assessing reading accuracy and rate, emergent literacy skills (phonological 14 fluency, rapid automatized naming and working memory) and reading affect questionnaires 15 (reading self-concept and reading anxiety) were administered to the participants. 16 Results 17 Path analysis was used as the primary analytic approach. Results indicated a negative moderate 18 relation between reading self-concept and reading anxiety. The relations of working memory and 19 emergent literacy to reading self-concept and reading anxiety were shown to be primarily 20 indirect via word reading accuracy and reading rate. Girls report higher reading anxiety and 21 lower reading self-concept, despite higher performance in reading accuracy and no difference in 22 reading rate compared to boys. 23 Conclusions 24 The current results support the importance of examining reading affect and potential sources of 25 reading affect. Results suggest that reading self-concept and anxiety and their related skills 26 should be considered in designing reading intervention and instructions